El aporte del cambio climático en la manifestación de la fasciolosis en Sudamérica - Pérez Mazzali, M. (2022)
This paper encourages reflection and frank debate on the sense, responsibility and challenge that researchers in Environmental Medicine and Education face the challenge posed by climate change that affects the entire world. It causes lack of drinking water, decrease in food production, and/or increased mortality in humans and animals due to floods, droughts and variations in average temperatures. Climatic conditions regulate parasitosis. Climate change can directly impact the manifestation of these diseases. Fasciolosis is a zoonotic parasitosis caused by Fasciola spp. and is one of the most widely distributed geographically. It has an indirect cycle; its definitive hosts are mammals, including humans. The intermediate hosts are snails inhabiting aqueous environments (rivers, streams, ponds, etc.). There they reproduce and complete the parasite?s life cycle. Climate change generates favorable atmospheric conditions for infestation in areas where the presence of the snail was not feasible due to adverse conditions for its development or the existence of definitive hosts, which could lead to changes in human and animal health. It is necessary to create public alerts due to the probable presentation of new epidemiological manifestations involving zoonotic diseases.